Estratégias na composição eletroacústica audiovisual com imagens em movimento e sistema sonoro multicanal - Aguiar, Danilo Silva (2016)
This work was aimed to seek strategies and procedures to establish new possibilities for the convergence of sound and moving image in audiovisual electroacoustic composition. It was decided to depict spatial behaviours in a multi-channel sound system. In order to include this possibility concepts and procedures devised by other researchers were sought. Initially, I focused the approach on the proposals about \"Media Pairing\" ( presented in the paper by John Coulter (2007 and 2010). As the research evolved there was the need to broaden the scope of Coulter s approach incorporating concepts devised by several other researchers, such as Michel Chion, Denis Smalley, Diego Garro, Flo Menezes, Marcelo Carneiro de Lima and Silvio Ferraz. Works by composers who concentrated their efforts in the practice of audiovisual electroacoustic composition were analised. The study that was carried out provided tools for the composition of the audiovisual electroacoustic work \"The Gap in the Door\" in the context of this research. The work and the supporting references led me to present some reflections on the compositional results and the proposition of strategies, which resulted in a hybrid approach relating sound, image and sound spatialization.